Patient Education Materials for Immobilisation Masks in Radiation Therapy for Adult Head and Neck Cancer Patients: A Scoping Review - Lucy Wood; Ruby Holman; Uyen Nguyen; Helen Nguyen; Aurora Senaratna; Misha Adams; Apajok Apath (Journal of Cancer Education, 2024)
Immobilisation masks (IMs) are used for people with head and neck cancer (HNC) undergoing radiation therapy (RT) treatment to ensure accuracy and reproducibility between treatments. Claustrophobia-related mask anxiety in HNC patients is common and can compromise treatment due to patient distress. This scoping review aimed to describe the content of publicly available Patient Education Materials (PEMs) for people with HNC undergoing RT. Three search engines (Bing, Yahoo, and Google) were systematically searched using standard terms. PEMs in audio-visual or written formats were eligible for inclusion if the target readership was adults with HNC and included content on IMs for RT. Content was appraised using the Patient Education Materials Assessment Tool for Printable and Audio-Visual Materials to assess understandability and actionability. In total, 304 PEMs were identified of which 20 met the inclusion criteria. Sixteen PEMs were webpages, three were PDF format, and one was a standalone video. The understandability and actionability of PEMs ranged between 47 to 100% and 0 to 80%, respectively. PEMs authored by Foundations/Organisations scored higher in understandability (80–100%) and were more likely to discuss mask anxiety coping strategies. In comparison, News sites and IM manufacturers published PEMs with the lowest understandability scores (20–80%). The significant variations in the quality of IM PEMs identified suggest that some sources may be more effective at informing patients about IMs. Although multiple aspects of the PEMs were consistent across the reviewed materials, many PEMs lacked information, and a stronger focus on understandability and actionability is required.